2014
DOI: 10.1186/s12887-014-0309-0
|View full text |Cite
|
Sign up to set email alerts
|

Improved nutrient intake following implementation of the consensus standardised parenteral nutrition formulations in preterm neonates – a before-after intervention study

Abstract: BackgroundNew standardised parenteral nutrition (SPN) formulations were implemented in July 2011 in many neonatal intensive care units in New South Wales following consensus group recommendations. The aim was to evaluate the efficacy and safety profile of new consensus formulations in preterm infants born less than 32 weeks.MethodsA before-after intervention study conducted at a tertiary neonatal intensive care unit. Data from the post-consensus cohort (2011 to 2012) were prospectively collected and compared r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 18 publications
1
11
0
Order By: Relevance
“…Results from recent studies have highlighted the importance of optimal nutrition intake during the first week of life to prevent cumulative energy deficits . Protein and energy intakes during the first week have been shown to have a major impact on outcomes associated with short‐term morbidities, improved growth and neurological development . Consistent with findings in these studies, we observed low energy and protein intakes in infants with hsPDA and a correlation between decreased fluid intake and lower energy and protein intakes after hsPDA diagnosis.…”
Section: Discussionsupporting
confidence: 89%
“…Results from recent studies have highlighted the importance of optimal nutrition intake during the first week of life to prevent cumulative energy deficits . Protein and energy intakes during the first week have been shown to have a major impact on outcomes associated with short‐term morbidities, improved growth and neurological development . Consistent with findings in these studies, we observed low energy and protein intakes in infants with hsPDA and a correlation between decreased fluid intake and lower energy and protein intakes after hsPDA diagnosis.…”
Section: Discussionsupporting
confidence: 89%
“…More and more data advocate intake safety from the 1 st day of standard nutrition which contains phosphates. [26][27][28] However, phosphorus supplementation is currently recommended from the 3 rd day of life; before that, neonates receive only a small amount of phosphorus in a lipid solution. Fears of early phosphate intake result from the need to intake sodium and potassium simultaneously, which is not recommended in the first days of life until diuresis stabilizes.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that the necessity for daily laboratory tests for monitoring parameters such as electrolytes is a question to be evaluated through quality improvement activities, particularly for the smallest preterm infants, who are at high risk of iatrogenic anemia. In consideration of the resources needed to administer PN, including personnel and cost, an area that remains unanswered is whether standardized PN admixtures in neonatal populations are safe and cost‐effective 27 . ‐ 30 With increased support for outcomes research in hospital settings, it should be expected that addressing nutrition will lead to improved care with fewer resources.…”
Section: Question 14: How Should Healthcare Organizations Track/monitmentioning
confidence: 99%